Qualitative and quantitative aspects of Sagitta elegans biology in the Okhotsk Sea - A. F. Volkov (Известия ТИНРО, 2018)
Data on abundance and biomass of mass arrowworm Sagitta elegans in the Okhotsk Sea are presented, by size classes, on the base of plankton surveys conducted by Pacific Fish. Res. Center (TINRO) in 1984–2017. S. elegans spawns throughout the year, with varying intensity by areas. The juveniles with the length < 6 mm are observed in mass along the eastern boundary of the sea in winter and spring, and in its entire periphery in summer. The mean annual portions of the size classes by abundance/biomass are: < 6 mm — 13.9/0.3 %; 6–10 mm — 10.0/1.9 %; 10–15 mm — 8.1/3.3 %; and 15–25 mm – 58.0/70.0 %. In the epipelagic layer 0–200 m, the total number of S. elegans depends negatively on the bathymetry: its mean abundance/biomass decreases from 71 ind./m3 and 942 mg/m3 in the zone with depth 30–50 m to 8 ind./m3 and 159 mg/m3 in the deep-water zone; the decreasing is more prominent for small-sized classes, and is not observed for the class > 25 mm. However, no more than 20 % of the species biomass is presented in the epipelagic layer, but the main part is concentrated in the layer 200–1000 m. S. elegans consumes the prey with the size equal to width of its mouth, mostly copepodites on different stages of development — their size correspondence to the size classes of arrowworms is presented, as well as the mean annual spatial distribution of small-, medium-, and large-sized copepods. Generally, the prey for the arrowworms with length < 25 mm (eggs, nauplii, smalland medium-sized copepods) is more abundant on the shelves, whereas the prey for the biggest arrowworms (large-sized copepods with length up to 5 mm) are concentrated in the deep sea.